The effectiveness of promotion tools in enhancing the customer awareness “Study in Rasamas Restaurant” / Mohd Khushairy Ahmad Shaifudin - Ahmad Shaifudin, Mohd Khushairy (Faculty of Business and Management, 2008)
This project paper which entitled ‘The Effectiveness of Promotion Tools In Enhancing Customer Awareness “Study In Rasamas Restaurant”’ purposely to study the influence of promotion tools used by Rasamas restaurant which is advertising, sales promotion and public relation in order to enhance the customer awareness. From this research, the researcher can identify the major problems that always faced by Rasamas and searching for effective solution on it matter arises. This report outlining the introduction, literature review, findings, analysis, conclusions and recommendations based on the questionnaire distributed to customers at Rasamas restaurant Alamanda Putrajaya. Three hypotheses have been tested by using correlation Analysis. Based on the hypotheses testing, the research has found that there is no influence between independent and dependent variables. In general, the objective of this study have been achieved regarding on most of the respondents are moderately aware about the promotion done by Rasamas restaurant.